2018
DOI: 10.2174/1567205015666180223093020
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Decreased Mitochondrial Superoxide Dismutase 2 and Peroxiredoxins 1 and 4 Based Mechanism of Concurrent Activation of AMPK and mTOR in Alzheimer’s Disease

Abstract: Collectively, we conclude that AMPK and mTOR metabolic axis is highly activated in AD brains. While the inhibitory link between AMPK and mTOR seems to be disrupted, we suggest oxidative stress as the underlying mechanism for concurrent activation of AMPK and mTOR in AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 0 publications
1
34
1
1
Order By: Relevance
“…In particular, Prdx1 eliminates hydrogen peroxide produced during cellular metabolism [54] and participates in cell survival by enhancing the expression of the pro-survival factor protein kinase B (PKB) [55]. The role of Prdx1 in AD has been recently highlighted by Majd et al who observed reduced levels of Prdx1 and 2 in postmortem brains of AD [56]; meanwhile, Schreibelt et al analyzed the functional role of Prdx1 using a brain endothelial cell line overexpressing Prdx1 and showed that enhanced Prdx1 expression in brain endothelial cells increased BBB integrity and reduced monocyte adhesion to and migration across a brain endothelial cell layer [57]. …”
Section: Discussionmentioning
confidence: 99%
“…In particular, Prdx1 eliminates hydrogen peroxide produced during cellular metabolism [54] and participates in cell survival by enhancing the expression of the pro-survival factor protein kinase B (PKB) [55]. The role of Prdx1 in AD has been recently highlighted by Majd et al who observed reduced levels of Prdx1 and 2 in postmortem brains of AD [56]; meanwhile, Schreibelt et al analyzed the functional role of Prdx1 using a brain endothelial cell line overexpressing Prdx1 and showed that enhanced Prdx1 expression in brain endothelial cells increased BBB integrity and reduced monocyte adhesion to and migration across a brain endothelial cell layer [57]. …”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer's disease (AD) is the leading cause of dementia worldwide, and AD patients and their families urgently require novel therapeutics to prevent and slow the progression of this devastating disorder. Hallmarks of AD include amyloid-␤ (A␤) peptide secretion and deposition into neuritic plaques, tau protein hyperphosphorylation and neurofibrillary tangle formation, metal ion dyshomeostasis [1][2][3][4][5][6][7][8][9], oxidative stress and lipid, nucleic acid, and protein damage [10][11][12][13], abortive cell cycle reentry [14][15][16][17][18][19][20][21][22][23][24][25][26], neuroinflammation and microbial dysbiosis [27][28][29][30][31][32][33], insulin resistance [34,35], cerebrovascular dysfunction [36][37][38], synaptic dysfunction [39,40], neuronal loss, endoplasmic reticulum stress [41][42][43][44], and mitochondrial dysfunction [...…”
Section: Introductionmentioning
confidence: 99%
“…PGC1␣ upregulates multiple antioxidant genes, including mitochondrial manganese superoxide dismutase (MnSOD), when bound to Forkhead box O3a (Foxo3a) and deacetylated by Sirtuin-1 (SIRT1) [69]. However, PGC1␣ protein levels are significantly lower in AD patients' hippocampi compared to controls [48], and mitochondrial biogenesis and MnSOD expression are impaired there [45,48]. Sildenafil has the potential to reverse the hippocampal PGC1␣ suppression in AD.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, mitochondrial oxidative stress is directly associated with LC FR, and negatively affects neuronal viability leading to neurodegeneration (Sanchez-Padilla et al 2014). A key mitochondrial enzyme in this process is superoxide dismutase 2 (SOD2) which provides protection against AβO-mediated oxidative stress (Du et al 2019) and its expression is decreased in Alzheimer’s (Majd and Power 2018). We therefore assessed the association of AβO-NU1/2 expression with that of SOD2 in APP-PSEN1 mice.…”
Section: Resultsmentioning
confidence: 99%